Aerosol microphysics and chemistry reveal the COVID19 lockdown impact on urban air quality - Konstantinos Eleftheriadis (Nature Portfolio, 2021)
Abstract Air quality in urban areas and megacities is dependent on emissions, physicochemical process and atmospheric conditions in a complex manner. The impact on air quality metrics of the COVID-19 lockdown measures was evaluated during two periods in Athens, Greece. The first period involved stoppage of educational and recreational activities and the second severe restrictions to all but necessary transport and workplace activities. Fresh traffic emissions and their aerosol products in terms of ultrafine nuclei particles and nitrates showed the most significant reduction especially during the 2nd period (40–50%). Carbonaceous aerosol both from fossil fuel emissions and biomass burning, as well as aging ultrafine and accumulation mode particles showed an increase of 10–20% of average before showing a decline (5 to 30%). It is found that removal of small nuclei and Aitken modes increased growth rates and migration of condensable species to larger particles maintaining aerosol volume.